Safety and efficacy of del Nido cardioplegia in adult cardiac surgery: experience in NICVD - Raha, Sanjay Kumar; Hasan, M. Kamrul; Jahan, Hosne; Kana Biswas, Smriti; Alam, M. Saidul (International Journal of Research in Medical Sciences, 2023)
Background: Cardioplegia is used to induce and provide a depolarized diastolic cardiac arrest to provide a motionless surgical field. Del Nido cardioplegia solution has been used extensively in congenital heart surgery for more than 20 years and more recently for adults. This observational study was performed to assess the safety and efficacy of del Nido cardioplegia in adult cardiac surgery patients. Methods: Total 140 adult patients selected for cardiac surgical procedure i.e., coronary artery bypass grafting (CABG), valve surgery, or CABG with valve surgery no need requiring cardiopulmonary bypass (CPB) were purposively allocated into two groups: a) del Nido cardioplegia (n=70) and b) blood cardioplegia (n=70). Primary outcomes assessed myocardial preservation. Results: The study compared del Nido (A) and blood cardioplegia (B) groups. Mean ages were 49.5±7.86 and 48.9±6.79 years, respectively (p=0.5641). BMI (26.98±2.3 vs 27.2±2.14 kg/m2, p=0.4846) and comorbid factors, including smoking (48% versus 51%) were similar. Differences were lower hemoglobin in A (males: 11.7±1.18 versus 13.6±0.55; females: 10.2±0.58 versus 12.2±0.21, p<0.0001) and CPB/ACC times for isolated CABG (A: 112.40±15.75/78.45±11.65 versus B: 123.8±18.55/86.28±15.26 minutes, p=0.0001). Post-operatively, more blood loss occurred in A, but they had shorter mechanical ventilation, ICU stay, and hospital stay durations. Other variables, like 30-day mortality, were similar. Conclusions: Evidence from this study suggests del Nido cardioplegia use in routine adult cases may be safe, result in comparable clinical outcomes, and streamline surgical workflow. The trend for troponin should be investigated further because it may suggest superior myocardial protection with the del Nido solution.